PERAN MAJELIS TAKLIM DALAM PENINGKATAN PEMAHAMAN DAN PELAKSANAAN IBADAH MASYARAKAT SINDANGSARI SUBANG - Hendi Suhendi; Ira Wahyudi (Jurnal Al-Hikmah: Jurnal Dakwah, 2021)
This research is entitled "role of mother taklim assembly review on the understanding of worship in daily life in sindangsari village, kasomalang district, subang regency". An investigation to analyze the role of the existing assemblies in Sindangsari village in improving Understanding of Islam and community worship behavior, especially women in Sindangsari village. The method used in this research is qualitative Methods, while data collection includes: in-depth interviews, questionnaires or questionnaires, observations and documentaries Studies. This research is located in Sindangsari Village, Kasomalang District, Subang Regency. The result of this study is that it is known that the assemblies in Sindangsari Village have a role as a non-formal institution in the middle A community that provides considerable support for the development of understanding of the Islamic religion and can at least have a role in increasing understanding and influencing the improvement of worship behavior such as sunnah prayers and understanding of other worship.